Pengembangan e-LKM Berbasis Literasi Sains untuk Meningkatkan Dimensi Profil Lulusan pada Materi Suhu dan Kalor - Fajrianour Qoyimah; Yudha Irhasyuarna; Rizky Febriyani Putri (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
Critical reasoning and communication are key dimensions of the deep learning graduate profile that should be fostered in science education; however, these skills have not yet been optimally developed. This study aimed to produce a valid, practical, and effective science literacy-based electronic student worksheet (e-LKM) using Liveworksheets to enhance critical reasoning and communication skills regarding the topic of temperature and heat. A Research and Development (R&D) approach utilizing the ADDIE model was employed. The study subjects consisted of 32 students from class VII G at SMP Negeri 3 Banjarmasin. Data collection involved validation sheets, student response questionnaires, pre-test and post-test questions on critical reasoning, and communication skill observation sheets. The results indicated that the e-LKM achieved a validity score of 0.88, a practicality score of 90.05%, and an effectiveness score (based on n-gain) of 0,77, placing it in the high category. Consequently, the e-LKM is deemed valid, practical, and effective for use in science instruction.